Peripheral Blood Leukocytes and Serum Nested Polymerase Chain Reaction Are Complementary Methods for Monitoring Active Cytomegalovirus Infection in Transplant Patients - PD Andrade; MT Fioravanti; EBV Anjos; C De Oliveira; DM Albuquerque; SCB Costa (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Human cytomegalovirus is an important cause of morbidity and mortality in immunocompromised patients. Qualitative polymerase chain reaction (PCR) has proven to be a sensitive and effective technique in defining active cytomegalovirus infection, in addition to having low cost and being a useful test for situations in which there is no need for quantification. Real-time PCR has the advantage of quantification; however, the high cost of this methodology makes it impractical for routine use.